The Thoughts Construction of President Donald Trump in Making Foreign Policy to End the War between the US and Taliban - Muhammad Arif Ikhsanudin (Universitas Gadjah Mada, 2023)
The war between the US and the Taliban began after the 9/11 attacks in 2001. President Bush immediately sent US military troops to Afghanistan to capture the leader of the Al-Qaeda terrorist group, Osama bin Laden. It is known that President Obama was sheltered by the Taliban in Afghanistan. During the Obama’s administration, bin Laden was successfully killed in 2011. The war between the US and the Taliban will continue until President Trump’s leadership. He considers that the goals of this war have been realized, targeting Al-Qaida leaders and that nothing is profitable for the US in continuing the war. According to Trump’s thinking, in 2020 there will be a peace agreement between the US and the Taliban. To answer this fact, this article will use constructivist theory to explain the construction of Bush's thoughts, the result of which is the United States' political policy towards the war in Afghanistan. Therefore, this journal will discuss the construction of Trump’s thoughts on ending the long war between the US and the Taliban. So that this paper can see how Trump's thought construction can end the war and what the real impact is for the US. From this, it can be concluded that the result of Trump’s thought construction is to protect US citizens and interests in the economic and military fields.